(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Forensic odontology is a specialized subject which is a perfect amalgamation of forensic sciences and dental sciences. The subject employs various traditional and advanced digital methods for education and analysis purposes. Advent of 3-Dimentional (3D) scanning and printing technologies have majorly influenced forensic odontology community. The technology allows replications of evidence matters in both the virtual and physical realm. It allows experimentation with the replica models for development of new analytical protocols. The ever increasing popularity of digital education is also playing a major role in the development of this highly specific doctrine of science. The digital education techniques allows wide spread collaboration for common cause of teaching and development of the subject. It allows sharing of study material and 3D model of evidential